Historic domes in the Middle East and central Asia: A study on pointed discontinuous double-shell domes / Maryam Ashkan - Maryam , Ashkan (2010)
This research presents a developed geometric approach for deriving the typologies and geometries of discontinuous double-shell domes, specially pointed types, in Islamic architecture. In addition, common morphological and typological characteristics of Eastern domes are put forward. Firstly, an outline of the origin and development of Eastern domes are addressed since the early through to the late Islamic periods. Common formal architectural language of Eastern domes are established by estimation of 53 samples of domes amongst eight countries; these are Iran, Iraq, Afghanistan, Pakistan, Kazakhstan, Uzbekistan, Turkmenistan and Turkey. In this regard, multifold approaches for analyzing those samples are organized into two certain parts. Besides, using al-Kashi geometrical features, a four centerd profile as an initial shape is constructed based on new geometric parameters to deduce the geometric commonalities of two aspects of formal language (typologies and geometries) of such domes. Common geometric prototypes for typical profile shared by the study cases are generated and formulated according to a proposed system.